Scandinavian children’s television in the 1970s: an institutionalisation of ‘68’? - Helle Strandgaard Jensen (Strenae)
In my paper I investigate how the Scandinavian broadcasting corporations’ children and youth departments were influenced by the changes in norms for children’s media which happened around “68”. My analysis is influenced by new work on Scandinavian “68”, which has shown that institutions in the region were very receptive towards the ideas held by rebelling youth. I look at how radical ideas about children’s media culture made their way in to the well-established broadcasting institutions and what expression they found when negotiated in policy papers and concrete programs. The analysis is made in three steps. First I scrutinize the Scandinavian “68” historiography to find out which ideas that has been deemed prominent within the regions youth rebellion and how these can be operationalized for an analysis of children’s television. Secondly, I analyze one of the major events in Scandinavian “68” regarding children’s media: the publication of Gunilla Ambjörnsson’s Trash Culture for Children and the symposium at Hässleby Castle in 1969, which the Nordic Council initiated because of all the big debate the book caused. Thirdly, I investigate how the main points from the book and the subsequent symposium made their way into the children and youth departments of the national broadcasters in Sweden, Norway and Denmark, as well as the shared policies and programs made together by these departments within the Nordic broadcasting union, Nordvision.